GAMBARAN FUNGSI KOGNITIF PADA PASIEN RAWAT JALAN DENGAN RIWAYAT STROKE DI POLIKLINIK SARAF RSUP PROF. DR. R.D. KANDOU MANADO - Paparang, Tirzha N.; Mahama, Corry N.; Ngantung, Denny J. (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Stroke is a major cause of cognitive dysfunction. The incidences of cognitive dysfunction increase three-fold after strokes, usually involving impairement of abilities in visuo-spacial, memory, orientation, speech, attention, and performance functions. The rapid, practical, and approved examinations used to evaluate and confirm the decline in cognitive functions are the Mini Mental State Examination (MMSE), the Clock Drawing Test (CDT), and the Trail Making Test (TMT). This study aimed to reveal the cognitive functions of outpatients with stroke histories in the Neurology Polyclinic, Prof. Dr. R.D. Kandou Hospital Manado by using the above mentioned examinations. This was a descriptive study with a cross-sectional design conducted in November 2012. The results showed that there were 51 respondents who fulfilled the inclusion criteria consisting of 32 males and 19 females. The highest decline of cognitive function by age, the educational level, and employment was 60-79 years, more than 9 years of education, and retired workers, respectively. The results of the MMSE, CDT, and TMT examinations for cognitive impairment evaluation were as follow: MMSE 62.75%, CDT 56.86%, TMT A 96.08%, and TMT B 84.31%. Conclusion: Most of the outpatients with stroke histories in the Neurology Polyclinic, Prof. Dr. R.D. Kandou Hospital Manado showed cognitive impairments. Keywords: CDT, cognitive function, MMSE, stroke, TMT-A and B. Â Â Abstrak: Stroke merupakan penyebab utama gangguan fungsi kognitif. Insiden gangguan kognitif meningkat tiga kali lipat setelah stroke, dan biasanya melibatkan kemampuan visuospasial, memori, orientasi, bahasa, perhatian dan fungsi eksekutif. Pemeriksaan yang digunakan untuk mengevaluasi dan mengonfirmasi penurunanÂ fungsi kognitif yang cepat dan praktis namun bernilai tinggi ialah Mini Mental State Examination (MMSE), Clock Drawing Test (CDT), dan Trail Making Test (TMT). Penelitian ini bertujuan untuk mengetahui gambaran fungsi kognitif pada pasien rawat jalan dengan riwayat stroke di Poliklinik Saraf RSUP Prof. Dr. R.D. Kandou Manado. Penelitian ini bersifat deskriptif dengan cross-sectional design dan dilaksanakan selama bulan November 2012. Hasil penelitian memperlihatkan bahwa 51 responden memenuhi kriteria inklusi, terdiri dari 32 laki-laki dan 19 perempuan. Berdasarkan usia, tingkat pendidikan, dan pekerjaan, penurunan fungsi kognitif terbanyak pada usia 60-79 tahun, tingkat pendidikan terakhir >9 tahun, dan pekerjaan pensiunan. Hasil pemeriksaan MMSE, CDT, dan TMT terhadap fungsi kognitif responden ialah: MMSE 62,75%, CDT 56,86%, TMT A 96,08%, dan TMT B 84,31%. Simpulan: Sebagian besar pasien rawat jalan dengan riwayat stroke di Poliklinik Saraf RSUP Prof. Dr. R.D. Kandou Manado telah memperlihatkan gagguan fungsi kognitif.Kata kunci: stroke, fungsi kognitif, MMSE, CDT, TMT-A dan B.